Philosophy of Polygamy in Islam - Nazir, Dad Mohammad (Journal of Social Sciences - Kabul University, 2023)
Undoubtedly, the rulings of the holy religion of Islam are innate, i.e. religious rulings have been legislated in a way that is compatible with the requirements of human nature, because Allah almighty, who is the creator of mankind and at the same time the founder of religious commandments for mankind, is not possible to legislating the rulings in a way that is incompatible with the innate demands of man. Among them, the ruling of polygamy law. So, it is also innate and consistent with the innate demands of mankind. Therefore, in this article, efforts have been made to answer the question of what is the philosophy of the polygamy system in Islam.The hypothesis answering this question is that the polygamy system in Islam has many philosophies. The scientific purpose of this study is to answering the main question. Of course, this research is analytical-interpretive and has been developed using library studies, i.e. referring to the Holy Quran, the Old Testament (Torah), the New Testament (Gospel) interpretation books, hadith books, oriental books, scientific-research articles and the views of contemporary scholars. The findings of this study indicate that the purpose of the ruling polygamy law in Islam is to provide solutions to the social and moral problem caused by the, Monogamy system.